Rare case of gemination of mandibular third molar—A case report - S Sandeep; G Jeevan Kumar; Suraj Potdar; Rishabh Bhanot; Amit S Vathare; Rahul V C Tiwari; B Harshitha (Journal of Family Medicine and Primary Care, 2020)
Fusion and germination are the anomalies that occur due to some developmental eccentricity during the time of morpho-differentiation of the tooth bud and have a close resemblance to each other. The gemination is an attempt of the division of a single tooth into two and, hence, appears as an enlarged single tooth while the tooth count is normal when the affected tooth is counted as one. Its exact pathogenesis is ambiguous. This anomaly has been observed mostly in deciduous dentition as compared to that in permanent dentition. Gemination is rarely associated with the third molar and, hence, the terminology is arguable when this condition is seen in relation to the third molar. In the present article, a case of germination of mandibular third molar has been reported.